HPV and head and neck cancer: A comprehensive review - Pallavi Taneja; Monica C. Solomon (Oral Oncology Reports)
Human papilloma virus (HPV) has historically been implicated in the etiopathogenesis of cervical cancers in females. However, in recent times, HPV has been found to be increasingly associated with cancers of the oral cavity especially with oropharyngeal carcinomas. The epidemiology of HPV positive cancers is different than that of the HPV negative cases. Consequently, study of HPV has become the center of focus of many oral pathologists. The prognosis of HPV positive cancer is better and can be explained by several theories. The following is a narrative review of mechanism of oncogenesis by HPV, diagnosis, comparison of the prognosis and clinical features between HPV positive and negative cases, histological features and finally a brief overview of the management options of HPV positive cancers.